2010
DOI: 10.4236/health.2010.27118
|View full text |Cite
|
Sign up to set email alerts
|

Internal environment in cancer patients and proposal that carcinogenesis is adaptive response of glycolysis to overcome adverse internal conditions

Abstract: In a series of our recent studies, stress was found to induce simultaneously hypothermia and hyperglycemia. These conditions are beneficial to obtain prompt force which depends on the glycolysis pathway and to escape emergency. Since we have noticed that such conditions resemble the internal environment seen in some cancer patients, it was investigated whether such conditions were accompanied with other patients. We selected patients with early and advanced cancer. Body temperature and other parameters includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Fresh venous blood was obtained before and after the DZ application for the measurement of PO 2 , SO 2 , PCO 2 and hemoglobin, using i-STAT 300 F (i-STAT Corporation, East Windsor, NJ, USA) as previously described [4][5][6][7]. WBCs were measured using a hemocytometer and the May-Grünwald Giemsa stain method.…”
Section: Assessment Of Other Parametersmentioning
confidence: 99%
“…Fresh venous blood was obtained before and after the DZ application for the measurement of PO 2 , SO 2 , PCO 2 and hemoglobin, using i-STAT 300 F (i-STAT Corporation, East Windsor, NJ, USA) as previously described [4][5][6][7]. WBCs were measured using a hemocytometer and the May-Grünwald Giemsa stain method.…”
Section: Assessment Of Other Parametersmentioning
confidence: 99%
“…This hypothesis may provide insights into our own health. Hypothermia and lymphocytopenia, which are features of aquatic mammals with stressful evolutionary histories, are also characteristics of the internal environment of cancer patients [5] [6]. In Japanese people, the average axillary body temperature had decreased from 36.8˚C to 36.2˚C -36.3˚C during the last five decades in conjunction with an enormous change in lifestyle.…”
Section: A Medical Hypothesis: Excessive Adaptation Results In Relatimentioning
confidence: 99%
“…Adaptive responses are often induced by stress and we have previously reported an adaptive glycolytic response to adverse internal conditions [5] [6]. In addition, we have shown that both hypothermia and lymphocytopenia are induced by stress [3] [4].…”
Section: A Medical Hypothesis: Excessive Adaptation Results In Relatimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one of our patients, who was observed in this study, had a miscarriage soon after exercising in a cold water pool, possibly due to a cold stress-induced imbalance in autonomic nerve status (excess sympathetic nerve dominance) via hypothermia. Accordingly, our patients were advised to avoid stressful situations (e.g., overwork) and the use of hot-water bottles while sleeping, and advised to practice deep breathing several times a day to promote relax [14]. Psychological advice from a specialist, as well as medical support, may be beneficial for pregnant women.…”
Section: Psychological and Medical Advice Is Needed In Pregnancy Selfmentioning
confidence: 99%